Three essays on mutual funds and benchmarking - Loh, Yu Sheng (Nanyang Technological University, 2022)
In essay one, we introduce a five-characteristic benchmark model and benchmark this model against other characteristic-based and factor-based models commonly used in mutual fund studies. We find that characteristic-based benchmarks are better-specified and more sensitive than factor-based models. In particular, the five-characteristic benchmark stands out as the best-performing characteristic-based model. The performance of the five characteristic benchmark is also evident within subsample tests and when benchmarking passively-managed portfolios. In essay two, I study a group of mutual funds that while claiming to have an ESG-focused investment strategy, in fact score lowly on ESG-metrics. These pretentious ESG funds exist as a detriment to investors by not only being able to attract greater flows, but also deliver worse risk-adjusted performance, charge higher fees, and take on greater risk as compared to high-scoring ESG funds and non-ESG funds. In essay three, I study if Chinese mutual fund managers are affected by a bias arising from their ethnicity, where investors may perceive them as being the “model minority”. My findings support the claim of a positive bias, where Chinese-managed funds receive higher fund flows despite there being no significant differences in performance as compared to non-Chinese-managed funds